Strategies for Promoting the Adaptation of Freshmen to University during Emergency Remote Teaching: Self-regulated Learning Workshops and Online Platform Lt-kuraCloud - Casale, Karina Reche; Bettioli, Ana Luisa; Santos, Daniel Araújo da Silva; Graciola, Marilda Aparecida Dantas; Pelissoni, Adriane S. M.; Consoni, Juliana Barbosa; Marcondes, Fernanda Klein (Revista de Graduação USP, 2023)
In their first year at university, many students struggle to adapt due to a lack of study habits and the challenges of navigating new academic, personal, and economic demands. The COVID-19 pandemic added further obstacles with emergency remote teaching. To support incoming Dentistry students at University of Campinas, Piracicaba – SP, Brazil, the Student Support Service shifted in-person self-regulated learning workshops to an online format. Additionally, interactive lessons (IL) on the Lt-kuraCloud platform were used. This study, approved by the Ethics Committee of FOP, aimed to assess student perceptions of these strategies. The workshops covered four key topics: adapting to university life, setting academic goals, study techniques, and time management. IL provided explanatory texts, videos, and exercises with instant feedback, offering an alternative study method and formative assessment, as asynchronous activity. At the end of the first semester in 2020, 66 students rated the usefulness of the workshops and IL on a scale of 1 to 5, with 1 being not useful. They provided justifications. The workshops received an average rating of 3.83 ± 0.99, while IL received 4.76 ± 0.50. According to students, the workshops improved study organization, socio-emotional control, and academic socialization. IL lessons enhanced comprehension, retention, and knowledge application. In conclusion, students found these strategies beneficial for their learning experience.